Corporate Social Responsibility, Managerial Entrenchment and Privatization. Example of an Algerian Public Company - Gana-Oueslati, Emna; Labaronne, Daniel (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2011)
We focus on strategic choices of managers of a public port in Algeria. These choices are embodied in a policy of corporate social responsibility: quality certification, safety and environmen, public-private partnerships, investment citizens. We try to understand what prompted the managers of this company to move in this direction. We propose to interpret their managerial choices as the result of a policy of rooting. We suggest that this policy is likely to put them in a beneficial position on the day the privatization of port activities Algeria will return to the facts.